2020
DOI: 10.2217/fon-2020-0522
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Practice Patterns and Outcomes in Veterans with Relapsed/Refractory Diffuse Large B-Cell Lymphoma

Abstract: Aim: To describe practices and outcomes in veterans with relapsed/refractory diffuse large B-cell lymphoma. Patients & methods: Using Veteran Affairs Cancer Registry System and electronic health record data, we identified relapsed/refractory diffuse large B-cell lymphoma patients completing second-line treatment (2L) in 2000–2016. Treatments were classified as aggressive/nonaggressive. Analyses included descriptive statistics and the Kaplan–Meier estimation of progression-free survival and overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In our study, 17.4% ( N = 59/340) of 2L patients received autologous SCT with various salvage regimens, 13.5% ( N = 46/340) received R‐ICE, and 10.3% ( N = 35/340) received BR. These estimates are consistent with evidence reported in previous studies 7,15,16 . These treatment patterns highlighted notably lower uptake of therapies in later lines of treatment, including CAR‐T (9.9% in 3L and 11.8% in 4L).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, 17.4% ( N = 59/340) of 2L patients received autologous SCT with various salvage regimens, 13.5% ( N = 46/340) received R‐ICE, and 10.3% ( N = 35/340) received BR. These estimates are consistent with evidence reported in previous studies 7,15,16 . These treatment patterns highlighted notably lower uptake of therapies in later lines of treatment, including CAR‐T (9.9% in 3L and 11.8% in 4L).…”
Section: Discussionsupporting
confidence: 91%
“…5 These and other studies demonstrated that patients with R/R DLBCL experience suboptimal outcomes across later LOTs, highlighting the persistent need for additional, effective treatment options. 7,16 Accordingly, NCCN guidelines recommend clinical trials in instances where CAR-T therapy is inaccessible or not indicated for treatment in later LOTs. 23 One strength of our study is that we used the COTA oncology database with granular demographic and clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Despite these efforts, durable remission remains elusive for many, which results in disease relapse. [6][7][8] The limited treatment options for relapsed/refractory (r/r) DLBCL underscore an unmet clinical need, which urges the development of new therapies for this patient population. 6,9 Recent studies have shown the promise of managing r/r DLBCL with several novel therapies, including CD19-targeted chimeric antigen receptor (CAR)-T cell therapy and antibody-drug conjugates (ADCs).…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients are unable to achieve deep and lasting remission, which necessitates the application of second‐line salvage therapy and autologous hematopoietic stem cell transplant (auto‐HSCT) 4,5 . Despite these efforts, durable remission remains elusive for many, which results in disease relapse 6–8 . The limited treatment options for relapsed/refractory (r/r) DLBCL underscore an unmet clinical need, which urges the development of new therapies for this patient population 6,9 …”
Section: Introductionmentioning
confidence: 99%
“…Prior real-world studies of the treatment of relapsed or refractory LBCL are focused on DLBCL and out-ofdate, 15 focused on a limited population (eg, Medicare patients or veterans), [16][17][18] or confounded by inclusion of data from patients cured by first-line therapy. [19][20][21] In addition, data are limited on real-world treatmentrelated adverse events during second-line therapy that occur outside hospitalization for SCT.…”
Section: Introductionmentioning
confidence: 99%